Biosemiotic Literary Criticism - Coletta, W. John. author. aut Link
XIII, 271 p. 27 illus., 16 illus. in color.
Keywords: This volume is based to a large extent on the understanding of biosemiotic literary criticism as a semiotic-model-making enterprise. For Jurij Lotman and Thomas A. Sebeok, “nature writing is essentially a model of the relationship between humans and nature” (Timo Maran); biosemiotic literary criticism, itself a form of nature writing and thus itself an ecological-niche-making enterprise, will be considered to be a model of modeling, a model of nature naturing. Modes and models of analysis drawn from Thomas A. Sebeok and Marcel Danesi’s Forms of Meaning: Modeling Systems Theory and Semiotic Analysis as well as from Timo Maran’s work on “modeling the environment in literature,” Edwina Taborsky’s writing on Peircean semiosis, and, of course, Jesper Hoffmeyer’s formative work in biosemiotics are among the most important organizing elements for this volume. .